2013
DOI: 10.1103/physrevlett.110.055503
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Impurity Induced Step Pinning and Recovery in Crystal Growth from Solutions

Abstract: We extend the terrace-step-kink model of crystal growth to impure solutions where the impurities act as barriers to step motion. The effects of supersaturation, step curvature, step repulsions, and impurities on step motion are treated in a unified free energy framework. The model reproduces several features seen in experiments on growth of potassium dihydrogen phosphate crystals, wherein a dead zone at low supersaturations and a recovery of crystal growth by motion of large coherent step bunches at larger sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Step bunches we observe in our simulations consist of single steps that have size of one unit cell, but also of macrosteps with size of multiple unit cells. Such formations are seen in experiments [24] and their time evolution remains subject of studies [25,26]. Macrosteps are created during the surface evolution process because there is no step-step repulsion incorporated into the model.…”
Section: Introductionmentioning
confidence: 96%
“…Step bunches we observe in our simulations consist of single steps that have size of one unit cell, but also of macrosteps with size of multiple unit cells. Such formations are seen in experiments [24] and their time evolution remains subject of studies [25,26]. Macrosteps are created during the surface evolution process because there is no step-step repulsion incorporated into the model.…”
Section: Introductionmentioning
confidence: 96%
“…In reality, steps do not display the smooth curvatures as assumed in their simplified model, but rather are discrete, atomistic objects subject to fluctuations. This was already realized by Frank [12] and explored further by van Enckevort and van den Berg [9] and more recently by Ranganathan and Weeks who developed a coarse grained terrace-step-kink model to study impurity induced step bunching [10,11].…”
mentioning
confidence: 94%
“…Such a dead zone occurs for a specific class of impurities, namely, those that are firmly adsorbed onto the surface with (near-) infinite residence times (Dynamic residues with finite residence times can in extreme cases lead to kinetic arrest, but only at very high concentrations.) The moments leading up to this growth cessation event have been the subject of intense study [4][5][6][7][8][9][10][11] and are thought to be well understood. The first theoretical description was developed as early as 1958 by Cabrera and Vermilyea (CV) [3], whose core views on the subject still persist today.…”
mentioning
confidence: 99%
“…From Monte Carlo simulations, Weeks and co-workers [5,8,9] were able to study twodimensional step motion and showed that mesh-like step bunch patterns are formed by step bunching. In their model, the effect of impurities is taken into account as a reduction in the probability of step advancing.…”
Section: Introductionmentioning
confidence: 99%